2016
DOI: 10.1152/physrev.00018.2015
|View full text |Cite
|
Sign up to set email alerts
|

Fear Memory

Abstract: Fear memory is the best-studied form of memory. It was thoroughly investigated in the past 60 years mostly using two classical conditioning procedures (contextual fear conditioning and fear conditioning to a tone) and one instrumental procedure (one-trial inhibitory avoidance). Fear memory is formed in the hippocampus (contextual conditioning and inhibitory avoidance), in the basolateral amygdala (inhibitory avoidance), and in the lateral amygdala (conditioning to a tone). The circuitry involves, in addition, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

16
279
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 381 publications
(298 citation statements)
references
References 662 publications
16
279
0
3
Order By: Relevance
“…Given the connections between the various amygdala subnuclei (38), our data fit with those of Gur et al (39), showing that Ani given into the medial amygdala disrupts SRM, and with those of Wang et al (40), who showed that lesion of the medial or basolateral amygdala impairs social but not other types of recognition in mice.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Given the connections between the various amygdala subnuclei (38), our data fit with those of Gur et al (39), showing that Ani given into the medial amygdala disrupts SRM, and with those of Wang et al (40), who showed that lesion of the medial or basolateral amygdala impairs social but not other types of recognition in mice.…”
Section: Discussionsupporting
confidence: 89%
“…Meanwhile, it can be concluded from the present data that the CA1 region of the dorsal hippocampus and the BLA are key participants in the regulation of SRM in rats, and that norepinephrine acting on β-receptors, dopamine acting on D1/D5 receptors, and histamine acting on H2 receptors in these two brain regions play a pivotal role in social recognition measured in a standard social discrimination paradigm. The roles of the catecholamines (14,18,38), and to an extent that of histamine (16,36), appear peculiarly interesting because they probably affect this (3) and other forms of memory (14) by actions in the hippocampus and BLA, mediated by the enhanced synthesis of the nuclear CREB (3,16,38), which is related to protein synthesis, here shown to be necessary for SRM, as previously posited by Kogan et al (3).…”
Section: Discussionmentioning
confidence: 71%
“…13 The circuitry involves, in addition, cortical structures such as pre-and infralimbic ventromedial prefrontal cortex (see Figure 1). 14 'Fear extinction' is a form of learning thought to underlie the suppression of fear memories. 15 Emerging evidence suggests that stress impairs recovery from trauma by impairing fear extinction, with various functional as well as structural abnormalities identified in the hippocampus, prefrontal cortex and amygdala.…”
Section: Biological Theoriesmentioning
confidence: 99%
“…Inactivation of the prelimbic and infralimbic subfields reduces fear expression to context and memory extinction, respectively (Corcoran and Quirk, 2007;Sierra-Mercado et al, 2011). In fact, it has been postulated that memory consolidation involves a time-dependent reorganization of activity in the PFC and associated limbic structures (hippocampus, amygdala and entorhinal cortex) (Preston and Eichenbaum, 2013;Izquierdo et al, 2016). In support to this, intra-PFC infusion of dopamine D1, amino-hydroxymethyl-iso xazole propionate (AMPA) and glutamate N-methyl-Daspartate (NMDA) receptor antagonists or infusion of camino-butyrate type A (GABA A ) agonist were shown to interfere with aversive memory consolidation at distinct time windows.…”
Section: Discussionmentioning
confidence: 99%